2017
DOI: 10.1016/j.juro.2017.02.1228
|View full text |Cite
|
Sign up to set email alerts
|

Pd27-07 Preoperative Transrectal Ultrasonographic Findings Can Predict the Improvement of the Peak Urinary Flow Rate After Surgical Treatment of Benign Prostatic Enlargement in Patients With Lower Urinary Tract Symptoms

Abstract: and recorded in accordance with the Clavien-Dindo classification system. Statistical analysis was performed using a Mann-Whitney U test. RESULTS: 969 cases of HoLEP were performed at our centre between December 2003 and October 2016. There was a statistically significant improvement in both urinary flow rate and post-void residual volumes (p<0.0001). Median pre-operative flow rate was 8.4ml/s (range 1-26.3) (n¼536) and post-operative flow rate was 19.5ml/s (range 1.8-68.4) (n¼649). Median pre-operative post-vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Patients with more IPP have been shown to benefit more from Holmium laser enucleation of the prostate (HoLEP) [47]. Also, Kim et al [13] and Park et al [48] found that patients with significant IPP benefit more than patients with non-significant IPP from Photoselective vaporization of the prostate (PVP). They had more significant early improvement in total IPSS, voiding IPSS sub-score and peak urinary flow rate.…”
Section: Ipp and Treatment Optionsmentioning
confidence: 99%
“…Patients with more IPP have been shown to benefit more from Holmium laser enucleation of the prostate (HoLEP) [47]. Also, Kim et al [13] and Park et al [48] found that patients with significant IPP benefit more than patients with non-significant IPP from Photoselective vaporization of the prostate (PVP). They had more significant early improvement in total IPSS, voiding IPSS sub-score and peak urinary flow rate.…”
Section: Ipp and Treatment Optionsmentioning
confidence: 99%